PEMANFAATAN MEDIA SOSIAL DALAM OPTIMALISASI PEMBELAJARAN DARING DI DESA GUNUNGPRING - Falakhunnisa Falakhunnisa; Qurotul Aini; Milna Wafirah (khidmatan, 2021)
Social media as a brave learning media is something that is still rarely done by the people of Gunungpring Village. Therefore, this time the assistance was carried out in an effort to optimize online learning by using social media. This empowerment assistance uses the ABCD (Asset-Based Community Development) approach using several stages: discovery, dream, define, design, and destiny. Because in this new normal era, parents are minimizing expenses, then the author provides a solution by using social media which is free but has many advantages, namely telegram. With the assistance program in the form of a telegram for learning media, it is expected that children use their original cellphones to play games, but now children are taught to use mobile phones to learn so that this potential can make children more effective in carrying out learning at home.